2020
DOI: 10.3390/jcm9103147
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil-Derived Neurotoxin, Tumor Necrosis Factor Alpha, and Calprotectin as Non-Invasive Biomarkers of Food Protein-Induced Allergic Proctocolitis in Infants

Abstract: Diagnosis of non-IgE mediated food allergy presents a special challenge due to lack of a single, non-invasive diagnostic method. We selected three fecal biomarkers of allergic inflammation of gastrointestinal origin in order to improve the diagnostic process. Twenty-seven infants with symptoms of hematochezia were prospectively enrolled into this study. All patients underwent a complete differential diagnosis of rectal bleeding. Non-IgE mediated food allergy was confirmed by an open, oral food challenge. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
0
15
0
2
Order By: Relevance
“…Children with FA demonstrated significantly higher FC and EDN levels than the controls ( p < 0.05). The authors found the best diagnostic performance in a combination of FC and EDN (88.9% and 84%) respectively and concluded that FC and EDN are reliable tools in differentiating between FPIAP and gastrointestinal functional disorders in infants [ 82 ].…”
Section: Fecal Biomarkersmentioning
confidence: 99%
“…Children with FA demonstrated significantly higher FC and EDN levels than the controls ( p < 0.05). The authors found the best diagnostic performance in a combination of FC and EDN (88.9% and 84%) respectively and concluded that FC and EDN are reliable tools in differentiating between FPIAP and gastrointestinal functional disorders in infants [ 82 ].…”
Section: Fecal Biomarkersmentioning
confidence: 99%
“…Two additional clinical cases have been reported [16,17], in which fEDN levels increased significantly after an oral challenge. Recently, a prospective study in infants 1-12 months of age found that median fEDN and fCP levels were significantly higher in 27 non-IgE-mediated food allergy (85% CMPA) children with hematochezia compared to a control group with functional disorders [18].…”
Section: Discussionmentioning
confidence: 99%
“…From the panel, they found EDN to be the most promising, highlighting as well the obvious need for studies with a higher population to confirm the results [88]. Other studies analyzing different combinations of these proteins also single out EDN as a potential biomarker for the diagnosis of these pathologies [92][93][94].…”
Section: Fecal Biomarkers Protein Analysismentioning
confidence: 98%